(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
The publishing industry has recently been involved into the digital revolution: digital editions are now the third element in publisher’s supply, in addition to the so-called ‘classics’ and the ‘front list’. It has caused many problems to publishers, especially in relation to 20th Century authors’ works, which are in catalogues from long time but are not considered ‘classics’ yet.